Sports policy factors leading to international sporting success - de Bosscher, V.; de Knop, P.; van Bottenburg, M.; Bingham, J.; Shibli, S. (2007)
This Digest is a summary report of a study to compare and analyse sport structures, policy and performance in six nations. The study developed from a concern about the lack of a model for comparing the efficiency and effectiveness of the ever-larger investments being made in high performance sport across the world. The research has been managed, and the report edited, by a consortium of researchers from the three nations involved in the first phase of the study - Belgium (Flanders), Netherlands and the UK. As the research gained momentum, the study broadened out to include Canada, Italy, Norway and the French-speaking part of Belgium (Wallony). The full report is being produced in book form and will be published in 2007.